Screening of Antenatal Patients for Anemia and Hemoglobinopathies - Tejal Vishandas Ahuja; Nidhi Bhatnagar; Mamta C. Shah; Sangeeta D. Shah (Global Journal of Transfusion Medicine, 2024)
Background and Objectives: Anemia is an extremely common condition in pregnancy worldwide, which confers several health risks to mother and child. Iron deficiency is the most widespread micronutritional deficiency in the world and disproportionately affects females because of increased iron requirements during menstruation, pregnancy, and lactation. Hemoglobinopathies are a group of inherited disorders because of abnormalities in hemoglobin (Hb) synthesis or structure. Thalassemia and sickle cell anemia are the most prevalent hemoglobinopathies and a national health burden in India so identifying these disorders during the antenatal period is necessary to take appropriate measures. This study aimed to ascertain the prevalence and spectrum of thalassemia/hemoglobinopathy amongst antenatal patients and also to analyze the ability of red cell indices to differentiate beta thalassemia trait from mild iron-deficiency anemia (IDA). Methods: A prospective study of screening for Hb variants in Antenatal Patients due to low Hb and evaluation of other causes was performed for 1 year with 570 samples. In low Hb, patients’ complete blood count, Reticulocyte staining, and sickling test were performed. Hb analysis was done by high-performance liquid chromatography Bio-Rad Variant II. In IDA Serum ferritin and Serum Iron level were done and in megaloblastic anemia (MA) Vitamin B12 levels were done. Results: The prevalence of anemia in antenatal patients was 90.25%; in this, IDA presented at 84.21%, MA at 4.73%, and dimorphic anemia at 1.27%. The prevalence of hemoglobinopathies in the current study was 9.75%; in this beta-thalassemia minor presented at 5.08%, sickle cell trait at 4.03%, Hb D Punjab at 0.52%, and Hb Q India at 0.17%. Conclusion: Antenatal screening for genetic disorders, such as beta-thalassemia and sickle cell anemia, aims to reduce the burden of these diseases by offering information to individuals with a high likelihood of giving birth to affected babies and giving parents more choices regarding their reproductive decisions. For this, premarital and antenatal screening should be mandatory to prevent the birth of affected offspring.